PECULARITIES OF THE PROGNOSIS ELABORATION OF SOME INDUSTRIAL BRANCHES AND FIELD - ANCA JARMILA GUŢĂ (Annals of the University of Petrosani: Economics)
The paper presents the principal indicators of territorial location of industry which are the purpose to realize a general orientation in the foundation of location decision of an enterprise in the analyzed territory. Also the paper proposes the manner in which, using some mathematical functions, we can model the development of some industrial subbranches. These functions are used in the prognosis studies for the extrapolation of dynamic rows of the industrial production included in the statistic data.